Defining and evaluating the ecological restoration economy. Issue 3 (13th April 2015) - BenDor, Todd K.; Livengood, Avery; Lester, T. William; Davis, Adam; Yonavjak, Logan
<x xml:space="preserve">Abstract</x> For decades, industry groups and many media outlets have propagated the notion that environmental protection is bad for business. However, missing from this public debate has been a detailed accounting of the U.S. economic output and employment that are created through conservation, restoration, and mitigation actions, which we call the "Restoration Economy." In this paper, we review related literature, including 14 local and state‐level case studies of privately funded environmental restoration projects. We also review federal and state government programs that fund restoration throughout the United States, revealing the complex nature of this sector. We find growing evidence that the restoration industry not only protects public environmental goods but also contributes to national economic growth and employment, supporting as many as 33 jobs per $1 million invested, with an employment multiplier of between 1.48 and 3.8 (the number of jobs supported by every restoration job) and an output multiplier of between 1.6 and 2.59 (multiplier for total economic output from investments). The existing literature also shows that restoration investments lead to significant positive economic and employment impacts and appear to have particularly localized benefits, which can be attributed to the tendency for projects to employ local labor and materials. While these initial figures are promising, the extent of environmental restoration activities and benefits at a national level is not yet well understood. Our findings reveal the need for a methodological framework for more accurately and broadly estimating the size of the U.S. restoration sector and its impact on the U.S. economy.